2019
DOI: 10.2478/bjmg-2019-0026
|View full text |Cite
|
Sign up to set email alerts
|

Association of VDR gene variant (rs1544410) with type 2 diabetes in a Pakistani cohort

Abstract: The present study was designed to measure the mean values of body mass index (BMI), random blood sugar/ fast ing blood sugar (RBS/FBS) tests, and Hb A 1c and to investigate the role of a genetic variant rs1544410 in the VDR gene in a Pakistani cohort. For this purpose, a total of 917 samples including 469 diabetes mellitus type 2 (T2DM), 145 DM type 1 (T1DM), and 303 healthy control were collected. Out of the total sample set, 500 individuals (250 T2DM cases and 250 controls) were genotyped for rs1544410. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…In addition, Barbara Angel and her colleagues reported that VDR polymorphisms are associated with type 2 diabetes in older individuals among the Santiago de Chile population (Angel et al, 2018). Further studies have concluded that there is an association between VDR polymorphisms and type 2 diabetes in different societies (Angel et al, 2018;Gendy et al, 2019;Khan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Barbara Angel and her colleagues reported that VDR polymorphisms are associated with type 2 diabetes in older individuals among the Santiago de Chile population (Angel et al, 2018). Further studies have concluded that there is an association between VDR polymorphisms and type 2 diabetes in different societies (Angel et al, 2018;Gendy et al, 2019;Khan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a study among residents of Pakistan demonstrated the association of VDR polymorphisms with the appearance of bone metabolism disorders [12]. Similar associations of VDR polymorphisms are also observed in other groups: Egyptian (rs7975232, rs2228570 and rs1544410), French (rs10735810), Canadian (rs10735810), and Tunisian (rs10735810) [13].…”
Section: Discussionmentioning
confidence: 55%
“…The current and previously published meta-analyses involving studies were shown in Table 2, Supplemental Digital Content, http://links.lww.com/MD/G216. 56 studies met our requirements, [26,27,28–34,19,35–80] of which 37 studies reported the VDR BsmI (5586 cases and 6484 controls), 31 studies examined the VDR FokI (6525 cases and 7464 controls), 19 studies investigated the VDR ApaI (2593 cases and 3557 controls), and 24 studies explored the VDR TaqI (3221 cases and 4027 controls) with T2DM risk, as shown in Figure 1 and Table 4, Supplemental Digital Content, http://links.lww.com/MD/G216. Among these studies, 25, 22, 6, and 4 of the studies were conducted to analyze Asians, Caucasians, Indians, and mixed populations, respectively.…”
Section: Resultsmentioning
confidence: 99%